Strategic considerations on the development of Central Asia - Banskota, Mahesh; Karki, Archana S.; Croon, Frank W. (Council for Sustainable Development of Central Asia, 1999)
Proceedings of 2nd CoDoCA Conference held in Urumqi, China, from September 13-18, 1998.